Incorporating cooperative learning into the Emancipated Curriculum in Indonesia: The English teachers’ perspectives - Rachmadhany, Clarita Dianmonica; Wulyani, Anik Nunuk; Setyowati, Lestari (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Diminished academic performance and an uptick in bullying necessitate heightened attention to fostering positive student interactions and skills. To address these issues, educators can effectively employ cooperative learning (CL) methods within their classes. This gap in the research underscores the need for a deeper investigation into the teachers’ implementations and weaknesses in CL practices. This research delved into the teachers’ understanding, implementations, and problems with CL in implementing Kurikulum Merdeka or Emancipated Curriculum (EC). It also examines how a professional development program influences teachers’ ability to integrate CL effectively. The twelve participants were English teachers from different places in Indonesia with diverse teaching career stages. A mixed-method approach was employed, involving questionnaires with statistical analysis using SPSS 30 and interviews through thematic analysis. Quantitative findings show that teachers’ activities align with the CL framework, while qualitative data reveal inconsistencies in actual practice. This contrast suggests a gap between perception and implementation, highlighting the need for targeted support to ensure meaningful CL application in classrooms.